Students’ And Teachers’ Perception And Attitude Of Using Ict In English Class In Globe School 1 Batam - Gabriela Jap; Gabriela Micheline Slikker (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Students at the private school in Batam are demonstrating promising trends in their use of technology for learning and adaptability. Other than that, the English teacher might still lack experience integrating ICT in the classroom, but the school's ICT resources are fully functional and ready for use. Because of the above urgency, using ICT in the classroom is mandatory for teachers. Further investigation is deemed necessary regarding the perceptions and attitudes of both students and teachers regarding the use of ICT in English classes at Globe 1 Batam. There is a pressing need to design this research on ICT use in the classroom because, in the twenty-first century, students will use it to meet ISTE standards and discover solutions for teachers who are still struggling to figure out how to integrate technology well enough to meet the standards for instructors as stated in the ISTE standards. The research design uses mixed-method research, this research uses the ASSURE model. In this study, which includes participants from the 9th and 12th grades as well as Ms. E, the English teacher at your partner school, a total of 24 students—13 from the 9th grade and 11 from the 12th grade—as well as Ms. E, the English teacher for Junior and Senior High school, highlight a challenge that Globe School faces in integrating technology usage in the classroom. By the time the school asks for assistance, this project has already been completed, and the researchers can offer advice on how to integrate ICT into English classes.